Condition of first-year students’ didactic adaptation within educational environment enriched with information and communication technologies - ISHCHUK, Nataliia; LIESOVYI, Volodymyr (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2014)
There being a contradiction between the didactic systems of comprehensive school and university, university teachers have to find solution to the problem of first-year students’ didactic adaptation. The wide use of ICT in doing every university course calls for adequate teaching methods and didactic conditions for students’ efficient progress in their first year of study at university. The article provides the condition of first-year students’ didactic adaptation within the educational environment enriched with ICT on the basis of the pilot research carried out at Vinnytsia Educational and Scientific Institute of Economics of Ternopil National Economic University. Although the results of the pilot research show students’ weaknesses of use of ICT, they prove the positive impact of the educational environment enriched with ICT on first-year students’ didactic adaptation, since it increases their didactic motivation and in many ways facilitates educational activities.